2010
DOI: 10.1007/s00300-010-0794-z
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the diatom genus Fragilariopsis in the Argentine Sea and Antarctic waters: morphology, distribution and abundance

Abstract: Fragilariopsis species composition and abun-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
85
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 42 publications
7
85
0
3
Order By: Relevance
“…The gross morphology of the cell and the valve ultrastructure of the strains examined in light and electron microscopy fit the descriptions provided for F. kerguelensis by different authors (Hasle, 1965(Hasle, , 1968Hasle & Syvertsen, 1997;Cefarelli et al, 2010). The ultrastructure of the poroid hymen of our specimens corresponds perfectly with the TEM images provided by Hasle (1965), thus further confirming the uniformity of the species.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The gross morphology of the cell and the valve ultrastructure of the strains examined in light and electron microscopy fit the descriptions provided for F. kerguelensis by different authors (Hasle, 1965(Hasle, , 1968Hasle & Syvertsen, 1997;Cefarelli et al, 2010). The ultrastructure of the poroid hymen of our specimens corresponds perfectly with the TEM images provided by Hasle (1965), thus further confirming the uniformity of the species.…”
Section: Discussionsupporting
confidence: 88%
“…The pioneering work carried out by Hasle (1965Hasle ( , 1968 did not include information on the number and ultrastructure of the girdle bands. Recently, Cefarelli et al (2010) reported the presence of one valvocopula and one girdle band in F. kerguelensis. We here provide evidence for the presence of an additional thin band at the abvalvar end of the cingulum; this band bears a ligula that inserts between the open ends of the first cingular band.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall distribution of apical axis length is right-skewed (see Figure 7 top Ca. 5.4% of all valves (505 in total) are sized outside the dimensions reported in the literature [16][17][18], depicted by the dashed rectangle in Figure 8.…”
Section: Resultsmentioning
confidence: 99%
“…To test whether the species shows a different distribution of apical axis lengths between this and the other MISs, Kolmogorov-Smirnov tests were used (see Tables A2 and A3). MIS 1 represents the most recent material we analysed and thus the best to be compared to the investigations of [16][17][18]. Between this and MIS 5 the two-sided test did not support a significant difference.…”
Section: Resultsmentioning
confidence: 99%